REPRESENTASI HEGEMONI PENGUNGGULAN MEREK DALAM WACANA IKLAN TELEVISI AIR MINUM GALON LE MINERALE - Silvana Zalista Nuraini Ghoyali; Laila Tri Lestari (Pendidikan Bahasa dan Sastra Indonesia, 2025)
The advertising of Le Minerale gallon mineral water responds to the dynamics of the advertising industry and the phenomenon of hegemonic ideology that emerges in a brand's effort to maintain its position by discrediting other brands, while demonstrating how the advertisement influences the public's perception of the brand and its products. Consequently, the aim of this research is to investigate the representation of hegemonic ideology in Le Minerale gallon television advertisements. Utilizing a qualitative descriptive approach, this study explores how the advertisement influences public perception of the brand and its products. Through analyses of denotative and connotative meanings in the advertisement discourse, the researcher identifies that Le Minerale highlights the safety, cleanliness, ease of use, and practical benefits of gallon-packaged drinking water as values desired by consumers. The research findings illustrate how the power of branding and marketing strategies can serve as tools to strengthen hegemonic ideology within a specific industry or market. In conclusion, Le Minerale's advertisement not only fulfills consumers' needs in terms of the product but also successfully creates an image that the brand is a desired solution for various demographics, reinforcing its position as a superior choice in the gallon-packaged drinking water category.